Bat Guano Carollia perspicillata is a source of Nitrogen Cycle Bacteria and its use as fertilizer: Guano del Murciélago Carollia perspicillata como una fuente de bacterias del ciclo del nitrógeno y su uso como fertilizante (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
Bat guano is considered a source of nutrients and bacteria that can act as a potential biofertilizer, associating vigorous growth of plants around where these mammals live, which today would be an environmentally friendly alternative, by reducing contamination by agrochemicals, the increase in production costs and meeting the demand for food acquisition. In Colombia, studies of bacteria that interact in bat guano, their potential as biofertilizers, the fixation of macro and micronutrients that interact in the endosphere and rhizosphere in symbiosis with plants are limited. The main objective of this research is to carry out a chemical and bacterial analysis of the nitrogen cycle of the Bat Guano Carollia perspicillata, analyzing its effectiveness with Phaseolus vulgaris (bean) cultures. The study place was La Palma-Cundinamarca, study population (Carollia perspicillata bat), a simple random sampling of the Guano was carried out in the rainy season and dry season and then an isolation of bacteria from the Nitrogen cycle was carried out in selective culture media. (MCN) and a chemical analysis of Nitrogen, Phosphorus and Potassium (NPK), identifying the bacteria Nitrobacter sp, Azotobacter sp and Nitrosomonas sp in the rainy season and Nitrosococcus sp in the dry season. Small-scale bioassays were carried out to analyze the biofertilizer potential of Guano with Phaseolus vulgaris (bean) crops, observing plant growth for a month, taking data every 7 days. The growth of Phaseolus vulgaris (bean) with the application of Guano showed double growth. Guano from Carollia perspicillata could be a good comprehensive fertilizer since it contains bacteria related to the Nitrogen Cycle and a high NPK.